Factor analysis of current liquidity of insurance company - Rohanova, Hanna (My University, 2019)
The study object is current liquidity of insurance companies. Analysis of their current liquidity makes it possible to find effective managerial solutions that are related to their development and solvency. One of the most problematic matters is how to identify those factors that affect their current liquidity and solvency. Using factor analysis, it has been developed a multiplicative current liquidity model, which includes 10 indicators: resource productivity of insurance; return on sales (ROS); current assets to total assets; insurance indemnity; insurance coverage; equity to total assets; return on assets (ROA); overall autonomy; reserves to premiums; current liabilities to total liabilities. Compared with similar known factor models, the proposed model allows identifying both the factors and direction of influence over the current liquidity in order to create an effective mechanism for managing solvency.
Keywords: current liquidity; solvency; insurance company; factor analysis; фінанси; кафедра фінансів